2020
DOI: 10.1530/jme-19-0158
|View full text |Cite
|
Sign up to set email alerts
|

STAT5 ablation in AgRP neurons increases female adiposity and blunts food restriction adaptations

Abstract: AgRP neurons are important players in the control of energy homeostasis and are responsive to several hormones. In addition, STAT5 signalling in the brain, which is activated by metabolic hormones and growth factors, modulates food intake, body fat and glucose homeostasis. Given that, and the absence of studies that describe STAT5 function in AgRP cells, the present study investigated the metabolic effects of Stat5a/b gene ablation in these neurons. We observed that STAT5 signalling in AgRP neurons regulates b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 66 publications
3
16
3
Order By: Relevance
“…Growth hormone-responsive neurones were identified in the present study via the expression of pSTAT5 in mice previously injected with GH. Although this method has been extensively used by our research group, 13,[15][16][17][18][19][29][30][31][40][41][42][43] we cannot guarantee that all pSTAT5 positive cells express GHR. Indeed, no study so far has demonstrated that TIDA neurones express Ghr mRNA.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Growth hormone-responsive neurones were identified in the present study via the expression of pSTAT5 in mice previously injected with GH. Although this method has been extensively used by our research group, 13,[15][16][17][18][19][29][30][31][40][41][42][43] we cannot guarantee that all pSTAT5 positive cells express GHR. Indeed, no study so far has demonstrated that TIDA neurones express Ghr mRNA.…”
Section: Discussionmentioning
confidence: 98%
“…15,[17][18][19][29][30][31]40 These studies revealed that GH has a particularly important action during situations of stress or when homeostasis is challenged. 41 For example, during food deprivation, GHR signalling in AgRP-expressing neurones triggers energy-saving adaptations to decrease weight loss and increase the chances of survival, 15,16 whereas, during hypoglycaemia, GH action on VMH neurones enhances the counter-regulatory response to recover blood glucose levels. 30 Interestingly, in most of the cases, GHR ablation in specific neuronal populations caused no or just minor physiological changes during basal conditions, 15,17,29,30 highlighting the impor- TH-specific GHR knockout mice that is secondary to increased GH secretion, as previously demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These areas include the arcuate nucleus (ARH), ventromedial nucleus (VMH), paraventricular nucleus of the hypothalamus (PVH), bed nucleus of the stria terminalis (BNST), central nucleus of the amygdala (CEA) and locus coeruleus [ 25 , 26 ]. In the ARH, GH acts in several distinct neuronal populations, such as neurons that express agouti-related protein (AgRP) [ 11 , 23 , 27 , 28 , 29 , 30 ], proopiomelanocortin (POMC) [ 31 ], tyrosine hydroxylase [ 32 , 33 ] or choline acetyltransferase [ 34 ]. The role of GHR signaling in these neuronal populations is starting to be unraveled.…”
Section: Introductionmentioning
confidence: 99%